Nonreciprocal single-photon state conversion between microwave and optical modes in a hybrid magnonic system - Jikun Xie; Shengli Ma; Yalong Ren; Xinke Li; Shaoyan Gao; Fuli Li (New Journal of Physics, 2023)
Coherent quantum transduction between microwave and optical signals is of great importance for long-distance quantum communication. Here we propose a novel scheme for the implementation of nonreciprocal single-photon state conversion between microwave and optical modes based on a hybrid magnonic system. A yttrium–iron–garnet (YIG) sphere with both the optomechanical and the optomagnetic properties is exploited to couple with a three-dimensional superconducting microwave resonator. The magnetostatic mode of the YIG sphere is treated as an intermediate to interact with the microwave and optical modes simultaneously. By manipulating the amplitudes and phase differences between the couplings via external driving fields, we show that the nonreciprocal microwave-light single-photon state conversion can be realized via the quantum interference effect.